2001
DOI: 10.1081/ada-100107664
|View full text |Cite
|
Sign up to set email alerts
|

RESIDENTIAL STATUS AND HIV RISK BEHAVIORS AMONG PUERTO RICAN DRUG INJECTORS IN NEW YORK AND PUERTO RICO*

Abstract: This article investigates the association between residential status and human immunodeficiency virus (HIV) risk behaviors among island and New York Puerto Rican injection drug users (IDUs). We assigned 561 subjects from New York City and 312 from Puerto Rico to five residential status categories: living in parent's home, living in own home, living in other's home, living in temporary housing (hotel, single-room occupancy [SRO] hotels), and homeless (living in streets/shelters). Dependent variables included in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 8 publications
2
21
2
Order By: Relevance
“…This lack of association may be accounted for by the challenges inherent in attempting to relate current or recent risks to prevalent outcomes. Relationships between current housing and recent injecting risk behaviors were more consistent, and fit with an extensive literature demonstrating associations between housing and a range of injection risk behaviors, 48,53,65,84,85 although it is notable that specific relationships have varied across studies. In our study, unstably housed participants were significantly more likely than their stably housed counterparts to report both recent public injecting and recent receptive sharing of injecting equipment other than syringes.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This lack of association may be accounted for by the challenges inherent in attempting to relate current or recent risks to prevalent outcomes. Relationships between current housing and recent injecting risk behaviors were more consistent, and fit with an extensive literature demonstrating associations between housing and a range of injection risk behaviors, 48,53,65,84,85 although it is notable that specific relationships have varied across studies. In our study, unstably housed participants were significantly more likely than their stably housed counterparts to report both recent public injecting and recent receptive sharing of injecting equipment other than syringes.…”
Section: Discussionsupporting
confidence: 70%
“…In our study, unstably housed participants were significantly more likely than their stably housed counterparts to report both recent public injecting and recent receptive sharing of injecting equipment other than syringes. Andia et al 84 likewise demonstrated that among Puerto Rican PWID homelessness was not associated with sharing syringes, but was associated with sharing other injecting equipment. Our results are consistent with previous research demonstrating that homeless PWID are more likely to inject in public spaces 43 ; and that public injecting is associated with frequent and hasty injecting and the sharing of injecting equipment.…”
Section: Discussionmentioning
confidence: 98%
“…The final measure was whether the study participant engaged in sex that involved the exchange of money. As reported in the work of Andia et al, 16 the first two measures have been widely identified as HIV transmission routes and the last two as circumstances in which behavior is likely to occur that enables HIV transmission.…”
Section: Methodsmentioning
confidence: 99%
“…This study was similar in key respects to those of Andia et al 16 and Song et al 18 in that it used the advantages of longitudinal data to examine the relationship between different housing statuses and specific HIV risk behaviors. This study, however, treated both housing status and risk behaviors as phenomena with occurrences that vary not only across IDUs, but also among individual IDUs over time.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation